REGISTER ANALYSIS USED BY SHIP'S PILOT IN PORT OF TANJUNG EMAS SEMARANG - Yulistiyani, Lita (2009)
This research is aimed at analyzing register used by ship's pilot in port of Tanjung Emas Semarang. The objectives of the study are to identify the forms and clarify the meaning of register used by ship's piloting in port of Tanjung Emas Semarang. In collecting the data, the writer uses observation, interview, and document. To identify the form of register, the writer refers to the theory of linguistic form, and to clarify the meaning by referring to the context of situation. The result shows the form of register. The writer finds three categories of form, they are: word, phrase and sentence. The word is in the form of 3 compound words and in the form of phrase are 2 verb phrase, 7 noun phrase, 5 adjective phrase, 1 present participle phrase, and 5 adverb phrase. Viewed from the meaning, the writer finds that the meaning of register used by ship' p pilot could be categorized into four, they are: (1) the real meaning is broader than the new meaning, (2) the new meaning is broader than the real meaning, (3) the new meaning and the real meaning are identical each other but they are used in different field. (4) the real meaning and the new meaning are quite different.